(untitled) (ENTHYMEMA, 2025)
This contribution aims to analyze Bachelard’s theory of moment and rhythm from a literary theory perspective. Firstly, we will examine the fundamental principles of Bachelardian reflection on temporality in La dialectique de la durée (1936). Secondly, we will analyze the Bachelardian essay “Instant poétique et instant métaphisique” (1939). Subsequently, we will observe the relevance of certain aspects of the French philosopher’s theory of moment and rhythm for his theory of literary imagination in the 1940s. In the conclusion, we will draw a comparison between Bachelard’s theory of poetic moment and rhythm and formalist, structuralist and post-structuralist thought.